2000
DOI: 10.1094/phyto.2000.90.8.834
|View full text |Cite
|
Sign up to set email alerts
|

Rational Management of Didymella rabiei in Chickpea by Integration of Genotype Resistance and Postinfection Application of Fungicides

Abstract: Various aspects of the integration of genotype resistance and chemical control of Ascochyta blight (caused by Didymella rabiei) in chickpea were examined in field experiments from 1993 to 1999 and in greenhouse experiments. Four commercially available chickpea cultivars representing a range of resistance to D. rabiei were used. The efficacy of chemical control in a highly susceptible cultivar was significantly (P < 0.01) related to the conduciveness of the environment to the pathogen. Adequate disease suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…These cultivars vary in their response to D. rabiei: 'Sfaradit' is highly susceptible; 'Ayala' is moderately susceptible; 'Hadas' is moderately resistant; and 'Bulgarit' is highly resistant (Shtienberg et al, 2000). Virulence tests were performed on detached leaves as described above.…”
Section: Didymella Rabiei In Israelmentioning
confidence: 99%
See 1 more Smart Citation
“…These cultivars vary in their response to D. rabiei: 'Sfaradit' is highly susceptible; 'Ayala' is moderately susceptible; 'Hadas' is moderately resistant; and 'Bulgarit' is highly resistant (Shtienberg et al, 2000). Virulence tests were performed on detached leaves as described above.…”
Section: Didymella Rabiei In Israelmentioning
confidence: 99%
“…Bulgarit (a highly resistant cultivar introduced to Israel from Bulgaria during the 1950s) or in cv-Hadas (a locally bred cultivar introduced in the late 1980s). These cultivars retain their resistance despite the repeated occurrence of severe epidemics in adjacent fields sown with susceptible cultivars., and despite the presence of the pathogen throughout all chickpea production areas in Israel (Shtienberg et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other Ascochyta diseases of legumes and Septoria diseases of cereals, Ascochyta blight of chickpea may cause total yield loss under the appropriate environmental conditions (43). Autumn-sown chickpea is severely affected by Ascochyta blight because the crop growth period coincides with the rainy season and optimum environmental conditions for pathogen development and spread (3,56).…”
mentioning
confidence: 99%
“…Any alteration in these factors would retard AB development. Rainfall and high relative humidity (> 95%) are critical for most epiphytotics, with temperature also playing an important role in development (Shtienberg et al, 2000). When the temperature is favourable and the moisture requirements of a pathogen on a susceptible host are fully met, an epidemic is likely to develop (Jhorar et al, 1998;Pande et al, 2005) which was observed during this survey.…”
Section: Resultsmentioning
confidence: 61%